LIFE PREDATOR: Prevent, detect, combat the spread of Silurus glanis in south European lakes to protect biodiversity - De Santis, Vanessa (2024)
The management of Invasive Alien Species (IAS) is often hindered by ecological, social and economic factors, resulting in inadequate biodiversity protection and inefficient use of public money. A clear example of such inefficient management in aquatic ecosystems is the European catfish Silurus glanis L. in southern Europe. Native to central Eurasia, S. glanis is an emblematic and controversial freshwater fish, being the subject of extensive and profitable trophy angling in central Europe and of commercial fishing in eastern Europe. Concurrently, in western and southern Europe where it was introduced in the XIX century, S. glanis is considered a problematic invader. The lack of comprehensive information on S. glanis invasive populations has limited effective management, which is critical to successfully control the spread and minimize negative impacts on native ecosystems and species. LIFE PREDATOR, started in September 2022 with a budget of € 2.85 million and a consortium of six partners from three countries, aims at developing a multidisciplinary and transnational approach to control established populations of S. glanis, and prevent further spreading and future introductions in southern European lakes and reservoirs. The project will develop and test an early warning system based on eDNA and citizen science and identify the most effective and selective capture techniques to reduce the abundance of catfish, particularly in Natura 2000 lakes, actively involving anglers and professional fishermen on this. Massive raising awareness campaigns will be conducted targeting anglers but also the general public, and protocols and best practices will be transferred to management authorities. For the long-term sustainability of the project, a South European Management Group will be created. Additionally, in northern Italy, where the catfish invasion is more advanced, a local circular economy will be implemented, involving the increase in fishing pressure by encouraging catfish consumption as food.